What is the influence of exacerbations on pulmonary function in pediatric and adolescent patients with severe asthma despite controller therapies? - A. Z. P. Brandão; L. M. L. B. F. Lasmar; L. M. A. S. Pertence; M. I. R. Vieira; G. B. Lasmar; V. O. Ganem; E. V. Mancuzo; M. V. N. P. de Queiroz (Clinical and Translational Allergy)
Abstract Background Although exacerbations are common in severe asthma, there have been few longitudinal studies evaluating their effect on lung function parameters. This study aimed to evaluate the impact of exacerbations on lung function in children and adolescents with severe asthma in Brazil. Methods This was a prospective study in which lung function parameters—forced vital capacity (forced vital capacity [FVC]), forced expiratory volume in 1 s (forced expiratory volume in 1 s [FEV1]), the FEV1/FVC ratio, and the forced expiratory flow between 25% and 75% of FVC (FEF25–75%), each expressed as a percentage of the predicted value—were measured at 3‐month intervals for three years in 64 patients (6–18 years of age) with severe asthma. Multivariate regression models of longitudinal data were employed to assess the associations between exacerbations and other predictors show with lung function parameters. Results The mean duration of prior use of an inhaled corticosteroid together with a long‐acting bronchodilator or other controller was 6.7 (SD 3.2) years. During the study period, 31 patients (48.5%) had exacerbations. We analyzed 479 pulmonary function tests and found no significant association between exacerbation and any of the lung function parameters: FEV1 (p = 0.90); FEF25–75% (p = 0.73); FEV1/FVC (p = 0.29); and FVC (p = 0.51). Passive smoking and being female were associated with mean FEV1 values that were 9.89% and 7.32% lower, respectively. Conclusions In children and adolescents with severe asthma who are using preventive treatment, exacerbations do not seem to be associated with impaired lung function.